Digital Resistance: How Online Communication Facilitates Responses to Racial Microaggressions. Issue 2 (April 2021) - Eschmann, Rob
Recent research finds negative impacts of racial microaggressions, defined as racial slights, on a variety of outcomes. Targets of racial microaggressions often report feeling pressured to remain silent in the face of these subtle interactions, which can be coded as aracial by perpetrators or bystanders. This article explores the ways Internet-based communication can change this dynamic and structure distinct responses to racial microaggressions. Drawing on in-depth interviews with undergraduate students of Color, I find that in some online spaces, students of Color have access to unique technology-based tools that increase their perceived and actual capacity to respond critically to racial microaggressions. I discuss implications for understanding online racial discourse and resistance on college campuses and beyond.